well you've got problems right out of the gate.
let's start with
\(\displaystyle \ln(x+3)\ln(2x+1)\)
\(\displaystyle \ln(x+3)\ln(2x+1)=\ln\left((2x+1)^{\ln(x+3)}\right)\)
and at \(\displaystyle x=4\) this becomes
\(\displaystyle \ln\left((2\cdot 4 + 1)^{\ln(4+3)}\right)=\ln(9^{\ln(7)})\)
punch this into your calculator or whatever and you get 4.2756 etc...
note for grins and giggles that also
\(\displaystyle \ln(x+3)\ln(2x+1)=\ln\left((x+3)^{\ln(2x+1)}\right)\)
at \(\displaystyle x=4\) this becomes
\(\displaystyle \ln(7^{\ln(9)})=4.2756...\)